Prevalence and Persistence of High-Growth Entrepreneurship: Which Institutions Matter Most? - Eva Christine Erhardt (Journal of Industry, Competition and Trade, 2022)
Which institutions encourage high-growth entrepreneurship to emerge and to be sustained? Building on institutional theory, this study exploits a sample of 239,911 observations for micro, small, and medium–sized firms from Bulgaria during the period 2001–2010 and finds three types of effects: first, informal institutional constraints such as corruption significantly reduce both the probability to become a high growth firm and the sustainability of growth. Second and unexpected from most of the literature, formal institutional constraints do not discourage firms from pursuing their growth ambitions and even enhance further growth. Third, constraints related to institutional governance, notably limited access to finance, have a negative effect before high-growth, but become less relevant after the high-growth spurt. Results imply that institutional reforms represent a policy tool for supporting high-growth entrepreneurship in an emerging economy context. They also suggest, however, that steadiness in reform efforts is necessary, as informal institutions, which matter most, are particularly slow to change.
Keywords: L25; D22; C18; P23; 690; High-growth entrepreneurship; Institutions; Job creation; Bulgaria